Priming by Timing: Arabidopsis thaliana Adjusts Its Priming Response to Lepidoptera Eggs to the Time of Larval Hatching - Valsamakis, Georgios; Bittner, Norbert; Fatouros, Nina E.; Kunze, Reinhard; Hilker, Monika; Lortzing, Vivien (Frontiers in Plant Science, 2020)
Plants can respond to eggs laid by herbivorous insects on their leaves by preparing (priming) their defense against the hatching larvae. Egg-mediated priming of defense is known for several plant species, including Brassicaceae. However, it is unknown yet for how long the eggs need to remain on a plant until a primed defense state is reached, which is ecologically manifested by reduced performance of the hatching larvae. To address this question, we used Arabidopsis thaliana, which carried eggs of the butterfly Pieris brassicae for one to six days prior to exposure to larval feeding. Our results show that larvae gained less biomass the longer the eggs had previously been on the plant. The strongest priming effect was obtained when eggs had been on the plant for five or six days, i.e. for (almost) the entire development time of the Pieris embryo inside the egg until larval hatching. Transcript levels of priming-responsive genes, levels of jasmonic acid-isoleucine (JA-Ile) and of the egg-inducible phytoalexin camalexin increased with the egg exposure time. Larval performance studies on mutant plants revealed that camalexin is dispensable for anti-herbivore defense against P. brassicae larvae, whereas JA-Ile – in concert with egg-induced salicylic acid – seems to be important for signaling egg-mediated primed defense. Thus, A. thaliana adjusts the kinetics of its egg-primed response to the time point of larval hatching. Hence, the plant is optimally prepared just in time prior to larval hatching.